THE DEVELOPMENT OF RESERVOIR SIMULATION METHOD FOR MICROBIAL ENHANCED OIL RECOVERY BASED ON LABORATORY DATA - ANDALY METAL BITTICACA (NIM: 222 10 074), LASKARY
MEOR (Microbial Enhanced Oil Recovery) is a method for increasing oil recovery (Enhanced Oil Recovery/EOR) using chemical compounds produced by microbes.With the lack of evidence of data field in Indonesia, while Indonesia reservoir condition is far more extreme than any other field that have applied MEOR, there is no reason to choose MEOR than any other EOR methods. There are many studies have indicated the proper technical procedures is necessary for the success of a pilot project testing. In this study the performance of biosurfactants produced by indigenous microbes of Field X, called Geobacillus toebii, is predicted using the simulator in accordance with the model of heterogeneous reservoir of Field X. Using KurniaÃ‚Â’s MEOR simulation approach on a commercial reservoir simulator, the results of research in the laboratory can be used as input data for the simulator. Modification on simulator schedule also conducted to model the huff-and-puff method. Reservoir simulation results are then used as a control methodology development of MEOR research in laboratory scale. Simulation results show an increase in cumulative oil production by 3.94% of incremental oil recovery after the secondary production phase. Increase in total production is a result of pressure maintenance after closing the well and the oil viscosity changes caused by microbial activity. Simulation results show the effective ability of MEOR in increasing oil production last about 3 months. The optimum concentration of biosurfactants is its CMC value. It can be predicted that the effective interfacial tension reduction by biosurfactants of indigenous microbes is 9.2%, which increases the cumulative oil production for 1784 STB.